TINDAK ILOKUSI DALAM FILM THE CHANGE-UP KARYA DAVID DOBKIN SUATU ANALISIS PRAGMATIK - Sondakh, Trisna M. M. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT This researchentitled â€œIllocutionary Act in the Film The Change-Up by David Dobkin: A Pragmatic Analysisâ€. It is an analysis ofÂ pragmatic investigation that focus on one aspect of speech acts called illocutionary act. It is an attempt to find the kinds and functions of illocutionary act in the film. The data have been taken from the characters utterancesâ€™ in the film. The writer analyzed the data descriptively by concentrating on utterances which contain illocution. The theory used in this research is taken from Searleâ€™s theory about illocutionary actsâ€™ classification. The findings of this research show that the kinds and functions of the illocutionary act are found in the film â€œThe Change-Upâ€. It is classified into five categories, those are assertives: stating, suggesting, vowing and reporting; directives: ordering, commending, requesting, and advising; commissives: promising and offering; expressive: thanking, praising, and blaming; declarations: naming, suspending, and declaring. Theoretically, the writer extends that this research can give any contribution for students or readers to understand kinds ofÂ illocutionary act and their functionsare not only in this film, but also in other literary works especially in daily communication. Keywords :Illocutionary,Â Speech act, Film, The Change-Up, Pragmatic Analysis. Â Â